The justices' manual, or, Guide to the ordinary duties of a justice of the peace in Newfoundland [electronic resource] : with appendix of forms - Prowse, D. W. (Daniel Woodley), 1834-1914. (St. John's, Nfld. : [s.n.], 1898)
"A vigilant magistracy, an accurate police, andan undeviating partiality in carrying the laws into execution ." Includes index. Electronic reproduction. Mode of access: Internet. 44